Research with children: reading of Emmanuel Lévinas and the otherness - Miranda, Francine Ramos de; Souza, Israel Fabiano Pereira de; Bastos, Paulo Roberto Haidamus de Oliveira; Marcheti, Maria Angélica; Ivo, Maria Lúcia; Carvalho, Alexandra Maria Almeida; Azevedo, Isabelle Campos de; Ferreira Júnior, Marcos Antonio (Revista Bioética, 2017)
Concern over delimiting research involving children, and more importantly the necessity of considering such research from an ethical perspective, is a recent development. With the aim of broadening this discussion, a form of ethical approach believed to be essential for the development of research with children was sought, based on the thinking of the philosopher Emmanuel Lévinas. Based on the otherness of Lévinas, it was concluded that for research with children, it is necessary to open oneself up to their world, and treat it as entirely diverse and autonomous. Understanding this necessity is to perceive the indispensability of otherness as an ethical presupposition of human relationships, in this case, between the researcher and the child. Only in this way will the autonomy, respect and active participation of the child be assured as a right not only in the role of a research participant but also a human being with individual characteristics that must be effectively considered.